Morphological revision of the Palaearctic species of the nominate subgenus Meloe Linnaeus, 1758 (Coleoptera, Meloidae), with description of ten new species - Pan, Zhao; Bologna, Marco A. (Zootaxa, 2021)
A morphological revision of the Meloe (Meloe) species from the Palaearctic Region, including the Transitional Chinese area is published. Groups and subgroups of species from the Palaearctic Region are defined for the first time and relationships with Afrotropical and Nearctic groups of species are discussed. Twenty-five species are considered, mostly after the examination of the types, with brief descriptions and figures of diagnostic characters. Ten species, from China and the Himalayan region, are described: Meloe chinensis n. sp., M. distincticornis n. sp., M. himalayensis n. sp., M. kashmirensis n. sp., M. kaszabi n. sp., M. lateantennatus n. sp., M. orientalis n. sp., M. poggii n. sp., M. shapovalovi n. sp., and M. xuhaoi n. sp. Both Meloe aegyptius and M. rathjensi are referred to M. proscarabaeus as subspecies. Four new synonymies are pointed out: M. sapporensis Kôno, 1936 and M. tenuipes Jakowlew, 1897 = M. proscarabaeus exaratus Faldermann, 1832; M. medogensis Tan, 1981 = M. arunachalae Saha, 1979; M. patellicornis Fairmaire, 1887 = M. lobatus Gebler, 1832. Lectotype of M. subcordicollis is designated. M. formosensis is tentatively maintained as distinct species, with the suggestion that it could be a subspecies of M. gracilior. Meloe menoko is tentatively included in the intraspecific variability of M. auriculatus, a formal synonymy will be made by other authors. Meloe poteli is not considered in this revision, being the type is unavailable; other species (M. modestus, M. longipennis, M. elegantulus), previously considered in the nominate subgenus are excluded. A key to both sexes of the species is carried out and a catalogue of localities is recorded as Appendix 1. Ecological information about phenology, elevation range, host plants, is summarized in a table, and some biogeographical remarks are proposed.